Microsoft Expression Web - Warner, Janine, 1967-; Safari eBooks ([S.l.] : Total Training, 2007)
"If you have already watched the training inside the Microsoft Expression Web product box, you have a great head-start. Get 8 more hours of new videos with self-guided lessons from Total Training that will open your eyes to the numerous capabilities of Microsoft Expression Web. Whether you are creating your very first web site or looking for advanced tips on how to create designs with Cascading Style Sheets (CSS) you will find your solution in this library of comprehensive video tutorials"--Resource description page.
Title from resource description page (viewed Oct. 2, 2009).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Microsoft Expression Web; Web sites -- Authoring programs; Electronic books